The impact of handling technique and handling frequency on laboratory mouse welfare is sex-specific - Sensini, Federica; Inta, Dragos; Palme, Rupert; Brandwein, Christiane; Pfeiffer, Natascha; Riva, Marco Andrea; Gass, Peter; Mallien, Anne Stephanie (Scientific reports, 2020)
Handling is a well-known source of stress to laboratory animals and can affect variability of results and even compromise animal welfare. The conventional tail handling in mice has been shown to induce aversion and anxiety-like behaviour. Recent findings demonstrate that the use of alternative handling techniques, e.g. tunnel handling, can mitigate negative handling-induced effects. Here, we show that technique and frequency of handling influence affective behaviour and stress hormone release of subjects in a sex-dependent manner. While frequent tail handling led to a reduction of wellbeing-associated burrowing and increased despair-like behaviour in male mice, females seemed unaffected. Instead, they displayed a stress response to a low handling frequency, which was not detectable in males. This could suggest that in terms of refinement, the impact in handling could differ between the sexes. Independently from this observation, both sexes preferred to interact with the tunnel. Mice generally explored the tunnel more often than the tail-handling hands of the experimenter and showed more positively rated approaches, e.g. touching or climbing, and at the same time, less defensive burrowing, indicating a strong preference for the tunnel.
Gesehen am 09.09.2024